Solasi Senyawa Bioaktif Golongan Flavonoid dari Getah Kemenyan Sumatra (Styrax benzoin) - Elizabet Silaban; Manihar Situmorang (Universitas Pahlawan Tuanku Tambusai, 2026)
Sumatran benzoin resin (Styrax benzoin) is a non-timber forest product with strong potential as a source of bioactive compounds, particularly flavonoids known for their antioxidant properties. However, studies on flavonoid isolation from this resin remain limited. This study aims to isolate flavonoid fractions, determine total flavonoid content of benzoin resin extract.The method involved extraction by maceration using 70% methanol, followed by isolation processes including phytochemical screening, Thin Layer Chromatography (TLC), Vacuum Liquid Chromatography (VLC), and column chromatography. Functional group identification was conducted using FTIR analysis. Total flavonoid content was determined using a spectrophotometric method with quercetin as the standard, resulting in a linear calibration curve with an R² value of 0.989. The results showed an average total flavonoid content of 6.0381 mgQE/g extract.Overall, the findings indicate that the methanol extract of benzoin resin contains a relatively high level of flavonoids. These results suggest that benzoin resin has promising potential to be developed as a natural source for health and pharmaceutical applications.